Nurse-led Interventions to Enhance Adherence to Chronic Medications (The International Journal for Scientific Research, 2023)
Introduction: Chronic diseases require long-term medication adherence to achieve optimal health outcomes, yet non-adherence remains a significant challenge. Nurse-led interventions have been proposed as a strategy to enhance adherence. This systematic review aimed to evaluate the effectiveness of nurse-led interventions in improving medication adherence among patients with chronic conditions. Methods: A comprehensive literature search was conducted across several databases, including PubMed, Embase, CINAHL, Cochrane Library, and PsycINFO, for studies published up to 2022. Only interventional studies and clinical trials led by nurses focusing on chronic medication adherence were included. The selection process involved screening for relevance, assessing methodological quality, and extracting data on adherence rates, intervention types, and patient outcomes. Results: Eight studies met the inclusion criteria, revealing a variety of nurse-led interventions, such as personalized counseling, telehealth follow-ups, educational workshops, and digital reminders. Sample sizes ranged from 30 to over 500 participants. The interventions demonstrated a significant improvement in medication adherence, with increases ranging from 15% to 25%. Specific interventions, like personalized care plans and technology-enhanced strategies, showed particular promise.Comparative analysis with other non-nurse-led interventions in the literature suggested that nurse-led approaches are at least as effective, with some evidence indicating superior outcomes in certain contexts. Conclusions: Nurse-led interventions are effective in enhancing medication adherence among patients with chronic diseases. The review highlights the importance of personalized and technology-enhanced approaches within these interventions. Despite limitations such as study heterogeneity and potential publication bias, the findings support the integration of nurse-led strategies into clinical practice to improve chronic disease management. Future research should focus on identifying the most effective components of these interventions across diverse patient populations.
Keywords: Nurse-Led Interventions; Medication Adherence; Chronic Diseases; Clinical Trials; Personalized Care